COMPLIANCE CHALLENGES OF SMES: KEY AREAS OF DIFFICULTIES IN SALES AND SERVICE TAX 2.0 - Bidin, Zainol; Abdul-Jabbar, Hijattulah; Abdul Aziz, Saliza (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
The implementation of Sales and Service Tax 2.0 (SST 2.0) in Malaysia has posed various compliance challenges for Small and Medium Enterprises (SMEs). This study aims to investigate the specific areas of difficulty faced by SMEs in adhering to SST 2.0 requirements. The target population comprised SMEs operating in Malaysia, with a final sample of 127 respondents selected through a questionnaire survey. Descriptive analysis was employed to identify key problem areas. The findings reveal that the most significant challenge for SMEs is the need to upgrade their computerization systems (mean = 3.94, SD = 0.784), highlighting technological limitations that hinder efficient SST compliance. Additionally, the need to enhance accounting systems (mean = 3.91) and the increased burden of documentation for record-keeping (mean = 3.78) further demonstrate that administrative and system-related constraints are major obstacles. Knowledge gaps, including a lack of SST understanding (mean = 3.83) and limited familiarity with SST legislation (mean = 3.56), compound these operational challenges. Other difficulties include uncertainty over the HS Code for taxable goods and services and the risk of double taxation within supply chains. These findings underscore the need for policymakers and tax authorities to address these challenges through targeted support. Recommended measures include providing clear guidelines, simplifying procedures, enhancing outreach and training, and offering incentives to help SMEs upgrade their technological and accounting systems. Such efforts are essential to improve SST 2.0 compliance rates among SMEs and to ensure the efficiency and sustainability of Malaysia’s tax system.